OPTIMIZATION OF FIBER BASED DISPERSION COMPENSATION IN RZ AND NRZ DATA MODULATION FORMATS - DIVYA DHAWAN; NEENA GUPTA (Journal of Engineering Science and Technology, 2011)
In this paper, dispersion compensating fibers are used to compensate for the positive dispersion accumulated over the length of transmission fiber. Pre and post dispersion compensation schemes are employed for dispersion compensation. Modulation formats employed are RZ and NRZ. The performance of these systems is analyzed and then the optimization of these schemes is done by varying the input powers of single mode fibers and dispersion compensating fibers. The investigation is done on detailed simulative analysis.